2017
DOI: 10.1002/elps.201600558
|View full text |Cite
|
Sign up to set email alerts
|

Molecular glycopathology by capillary electrophoresis: Analysis of the N‐glycome of formalin‐fixed paraffin‐embedded mouse tissue samples

Abstract: Capillary electrophoresis with laser-induced fluorescence (CE-LIF) detection was used to analyze endoglycosidase released and fluorophore-labeled N-glycans from formalin-fixed paraffin-embedded (FFPE) mouse tissue samples of lung, brain, heart, spleen, liver, kidney and intestine. The FFPE samples were first deparaffinized followed by solubilization and glycoprotein retrieval. PNGase F mediated release of the N-linked oligosaccharides was followed by labeling with aminopyrene trisulfonate. After CE-LIF glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…CE is a high-resolution method that can separate complex carbohydrate molecules while offering excellent sensitivity. This method, in conjunction with laser-induced fluorescence (LIF) detection, can reach detection limits in the femtomolar range [ 156 ] and is optimal for profiling fluorophore-labelled oligosaccharides [ 157 ]. Briefly, this analytical system used for carbohydrate profiling separates and analyses oligosaccharides released from glycoproteins.…”
Section: Glycomics Techniquesmentioning
confidence: 99%
“…CE is a high-resolution method that can separate complex carbohydrate molecules while offering excellent sensitivity. This method, in conjunction with laser-induced fluorescence (LIF) detection, can reach detection limits in the femtomolar range [ 156 ] and is optimal for profiling fluorophore-labelled oligosaccharides [ 157 ]. Briefly, this analytical system used for carbohydrate profiling separates and analyses oligosaccharides released from glycoproteins.…”
Section: Glycomics Techniquesmentioning
confidence: 99%
“…4.2b,c) (Hennig et al 2016;Schwedler et al 2014a, b;Chen et al 2017;Huang et al 2017;Guttman et al 2015)], along with position and linkage of fucose (Fuc) [e.g., α1-6 core Fuc from α1-3/1-4 Fuc on antenna N-acetylglucosamine (GlcNAc) or α1-2 Fuc on galactose (Hennig et al 2016;Konze et al 2017;Thiesler et al 2016;Weiz et al 2016;Schwedler et al 2014a)], type and linkage of sialic acids (Sia) [e.g., N-acetylneuraminic acid (Neu5Ac) from N-glycolylneuraminic acid (Neu5Gc), see Fig. 4.3d (Abeln et al 2017), and α2-3 from α2-6 (Hennig et al 2016;Konze et al 2017;Thiesler et al 2016;Donczo et al 2017;Meininger et al 2016)], and linkage of galactose (Gal) [e.g., β1-3 Gal from β1-4 Gal (Konze et al 2017;Thiesler et al 2016;Schwedler et al 2014a;Muñoz et al 2019)]. This feature becomes especially advantageous when thinking about the importance of determining immunogenic α-Gal and Neu5Gc on glycoprotein therapeutics (Chung et al 2008;Teranishi et al 2002;Van der Linden et al 2000).…”
Section: Background: Principles Of Capillary (Gel) Electrophoresis (C(g)e)mentioning
confidence: 99%
“…For mouse lung tissue, the effect of the elapsed time between the actual sampling and the formalin fixation, paraffin embedding process has been investigated to understand its influence on N ‐glycosylation degradation in zero time point as well as after 1 and 2 h of room temperature storage. All other mouse tissue sample specimens were profiled for their N ‐glycosylation since different tissue sample types have unique N ‐glycan profiles, specific to that particular organ containing diverse proportions of high and low sialylated, high mannose as well as neutral carbohydrate structures in different size ranges, and interestingly a few low degree of polymerization glucose oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier results revealed that the N‐linked carbohydrates of glycoproteins with neutral, sialylated and high mannose structures were not affected by the formalin fixation and paraffin embedding process . Thus, it was considered that the fixation process archived the N‐glycan structures and compositions of the sample at the very moment it was prepared.…”
Section: Introductionmentioning
confidence: 98%